Where is Abbas Kiarostami? toward a postcolonial film-philosophy - Dabashi, Hamid 1951- (University of California Press, 2025)
"When Abbas Kiarostami suddenly passed away in July 2016, he was already an iconic figure in world cinema-and his reputation as a master filmmaker has only grown since. In this book, celebrated scholar Hamid Dabashi offers a new way of looking at Kiarostami's art world, one that questions the very idea of film philosophy. Dabashi's authoritative account of the philosophical resonances of Kiarostami's oeuvre offers an iconoclastic critique of the field's Eurocentrism and, in vivid prose, makes the case for a new method of appreciating the work of this essential figure. The result is a provocative perspective on the totality of Kiarostami's legacy that, with deep roots in Iranian aesthetic and Persian poetic and philosophical traditions, overcomes film's provincial preoccupation with its Western heritage and charts a new path forward for film philosophy."--
Keywords: Kiarostami, Abbas -- 1940-2016; Philosophie; Spielfilm; Kiarostami, Abbas / Philosophy; Philosophy in motion pictures; Motion picture producers and directors / Iran; Motion pictures / Iran / Philosophy; Motion pictures / Iran / Aesthetics; Philosophie au cinéma; Producteurs et réalisateurs de cinéma / Iran; Cinéma / Iran / Philosophie; Cinéma / Iran / Esthétique